2011
DOI: 10.5588/ijtld.10.0741
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for accepting or refusing HIV services among tuberculosis patients at a TB-HIV integration clinic in Malawi

Abstract: Several factors that undermine uptake of ART have been highlighted; targeted measures urgently need to be addressed by TB-HIV programmes to overcome these barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 8 publications
1
32
1
Order By: Relevance
“…This may partly account for the considerable discrepancy between the nurses' impression that most of the TB patients are tested for HIV and started on ART if the test comes out positive, while the figures in the TB registers are much lower [6]. In contrast to literature from other countries [9,14], ARV availability was not a barrier in the facilities that participated in the study. Indeed, ARV availability in Namibia was reported as almost 100% in public facilities during the time period 2007-2010 [29].…”
Section: Barriers At the Health System Levelmentioning
confidence: 63%
See 2 more Smart Citations
“…This may partly account for the considerable discrepancy between the nurses' impression that most of the TB patients are tested for HIV and started on ART if the test comes out positive, while the figures in the TB registers are much lower [6]. In contrast to literature from other countries [9,14], ARV availability was not a barrier in the facilities that participated in the study. Indeed, ARV availability in Namibia was reported as almost 100% in public facilities during the time period 2007-2010 [29].…”
Section: Barriers At the Health System Levelmentioning
confidence: 63%
“…A semi-structured interview guide was developed based on a literature review [9][10][11][12][13][14][15][16][17][18][19]21] and pre-tested with Namibian healthcare professionals. The focus was a discussion of potential barriers to access to ART for HIV-positive TB patients in Namibia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results, however, are comparable to those found in a study in Malawi on adult TB patients, which reported that 51% of HIV-infected TB patients on ART had started HIV treatment before 2 months of TB treatment, 33% between 2 and 6 months and 16% after completion of TB treatment. 16 Whatever the reasons for early start of ART, it is evident from this study assessing outcomes under routine programme conditions that TB treatment success rates were better in patients who started ART early rather than later. The death rates of TB patients who started ART early were also considerably lower than in those who started later.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 Recommended programme strategies to reduce early mortality among TB patients include the provision of early HIV diagnosis and timely initiation of ART. [6][7][8][9] Mortality rates rose from 5.4 per 100 person-years (py) to 12.1/100 py when initiation of ART was delayed until the com-Bwaila Hospital (BH), and is supported by the Lighthouse Trust. The TB-HIV Integration Clinic, located at ZCH, is an expansion of the Ministry of Health (MoH) and Dignitas International collaborative ART Clinic at ZCH.…”
Section: Discussionmentioning
confidence: 99%